Not for King or country : Edward Cecil-Smith, the Communist Party of Canada, and the Spanish Civil War - Wentzell, Tyler, 1983- (University of Toronto Press, 2019)
"Nearly 1700 Canadians volunteered to fight in the International Brigades during the Spanish Civil War, yet there is not a single biography of a Canadian participant. Little is written about the Canadian volunteers, there are only 4 non fiction books and Michael Petrou's "Renegades" is scholarly. Edward Cecil-Smith, the commander of the ostensibly Canadian Mackenzie Papineau Battalian provides not only a case study of these volunteers, but a dramatic depiction of life in Canada during the 1930s."--